IV Ibuprofen for Prevention of Post-ERCP Pancreatitis in Children: A Randomized Placebo-controlled Feasibility Study. Issue 1 (January 2020) - Troendle, David M.; Gurram, Bhaskar; Huang, Rong; Barth, Bradley A.
ABSTRACT: Background: Post-endoscopic retrograde cholangiopancreatography (post-ERCP) pancreatitis (PEP) is reported to occur in up to 11% of pediatric patients. To date, no study has prospectively evaluated an intervention to prevent PEP in children. It is unclear if such a study is even feasible. Objective: The aim of the study was to evaluate the feasibility of studying IV ibuprofen for PEP prevention in the pediatric population. Methods: This was a prospective randomized double-blind placebo-controlled feasibility study. Patients younger than 19 years of age undergoing ERCP were randomized to receive 10 mg/kg IV ibuprofen (max of 800 mg) or placebo (saline) at the time of ERCP. The primary outcome was PEP. Secondary outcomes included post-ERCP–related bleeding, rates of other procedural and medication-related adverse events. Results: Fifty-eight patients were randomized and received either IV ibuprofen or placebo. Preprocedure- and procedure-related factors were not significantly different between the groups except that patients in the placebo group tended to weigh less (48.7 vs 63.7 kg, P  = 0.03). There were 7 episodes of PEP (12%). PEP was less frequently identified in the Ibuprofen group than in the control group (7% vs 17%), but this was not statistically significant ( P  = 0.42). Mean postprocedural abdominal pain scores were significantly lower in the IV Ibuprofen group than in the control group (1.1 vs 3.1, P  = 0.01) and the number of patients who had increased abdominal pain after the procedure was significantly lower in ibuprofen group than in the control group (3% vs 38%, P  = 0.002). There were no significant differences in procedure-related or drug-related adverse events. Conclusions: Postprocedural pain scores and the number of patients who had increased abdominal pain after the procedure were significantly lower in the IV ibuprofen group. The current study provides encouraging, but only very weak evidence that IV ibuprofen decreases PEP in children. Power analysis suggests that a small handful of high-volume pediatric centers would be able to perform an adequate clinical trial in a reasonable time frame. Focusing on all cause postprocedural pain (PEP and non-PEP) may allow for a more efficiency study design and be just as clinically relevant. Abstract : Supplemental Digital Content is available in the text